Black Box Testing pada Aplikasi Pencatatan Peminjaman Buku Menggunakan Boundary Value Analysis - Eno Hakimah Kusuma Dewi; Ilyas Shiddiq Pratama; Audy Sukma Putera; Carudin Carudin (Universitas Indraprasta PGRI Jakarta, 2022)
The book borrowing recording application can record activities related to borrowing books in the library, such as recording a track record of borrowing a book. However, applications that have been made in such a way need to go through a test flow to find out how far the performance and quality of the application itself is. Therefore, it is necessary to have a test to find out how the quality is. So, the purpose of this research is to carry out a testing on the book lending recording application to identify whether the application is in accordance with user needs or not. The test, which is one of the stages of the Software Development Life Cycle (SDLC) methodology carried out on this book lending recording application, applies Black Box Testing with the Boundary Value Analysis method which focuses on aspects of input validation, observing input content, and input results. The test results show that in the book borrowing recording system, discrepancies were found in the input process in the loan registration feature and book borrowing form so that it needed to be corrected before being used by the user.